Investigaciones arqueológicas en Tumshukayko (Caraz, Ancash) - Bueno Mendoza, Alberto (2005)
Tumshukayko is a gigantic monumental archeological place located in the outskirts of the north direction of the city Caraz, county of Huaylas, Ancash. It represents a true early urban concentration in a wide space, with a great dominat central mound, where we have begun the archaelogical excavations supported by the UNMSM.